Aliyatu Al-Tamasuki Al-Nashyi fi Al-Qurani Al-Karimi Wa Dalalutuha fi Tafsiri Al-Kassyafi - Osamah Saleh Mohammed Allbail; Rijal Mahdi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
This research aims to highlight the importance of context and its role in the coherence of the text and describe the coherence mechanisms revealed by Al-Zamakhshari during his interpretations. Al-Zamakhshari is considered one of the first who follow this aspect. The context is in its fate, giving it multiple meanings or limiting it to one meaning, and among the mechanisms mentioned by Al-Zamakhshari is the referral listing types and indicating its importance. The mechanisms are repetition and sympathy, and all of this will become clear during the research. The research followed a descriptive approach, but it did not remain a captive to it, but tried to benefit from other approaches as much as possible. The research has drawn conclusions from them; First: Although al-ZamakhshariÂ mention the word context only a few times, he used it a lot during his interpretation, as he deal with most contextual phenomena in an approach that reveals Zamakhshari's awareness of the importance of context in understanding the meaning. Second: Al-Zamakhshari realized the importance of text cohesion, and what repetition and referral bring about linking the text to each other. He took care of the assignee and the multiplicity of the assignee, which leads to the coherence of the text, this does not mean that he left it unchecked or restricted as he stresses the importance of taking into account the internal context and taking into account the Qurâ€™anic systems. And its linguistic function, and its usefulness for the addresses, as Zamakhshari believes that repetition is rhetorical unless it benefits the reader, or the speaker wants to deliver a message to the reader through him. Third: Al-Zamakhshari paid great attention to conjunctions, and al-Zamakhshari showed the ability of conjunctions to connect parts of the text.Â ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø¥Ø¨Ø±Ø§Ø² Ø£Ù‡Ù…ÙŠØ© Ø§Ù„Ø³ÙŠØ§Ù‚ ÙˆØ¯ÙˆØ±Ù‡ ÙÙŠ ØªØ±Ø§Ø¨Ø· Ø§Ù„Ù†Øµ ÙˆØªÙ†Ø§Ø³Ù‚Ù‡ ÙˆÙˆØµÙ Ø¢Ù„ÙŠØ§Øª Ø§Ù„ØªÙ…Ø§Ø³Ùƒ Ø§Ù„ØªÙŠ ÙƒØ´Ù Ø¹Ù†Ù‡Ø§ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ø£Ø«Ù†Ø§Ø¡ ØªÙØ³ÙŠØ±Ù‡ØŒ ÙˆÙŠØ¹Ø¯ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ù…Ù† Ø§Ù„Ø³Ø¨Ø§Ù‚ÙŠÙ† Ø¥Ù„Ù‰ ØªØªØ¨Ø¹ Ù‡Ø°Ø§ Ø§Ù„Ø¬Ø§Ù†Ø¨ØŒ ÙÙ‚Ø¯ Ø£ÙˆÙ„Ù‰ Ù‡Ø°Ø§ Ø§Ù„ØªÙ…Ø§Ø³Ùƒ Ø¹Ù†Ø§ÙŠØ© ÙØ§Ø¦Ù‚Ø©ØŒ Ø¥Ø° Ø°Ù‡Ø¨ Ø¥Ù„Ù‰ Ø¥Ø¨Ø±Ø§Ø² Ø±ÙˆØ§Ø¨Ø· Ø§Ù„Ù†ØµØŒ ÙˆØ¯Ù„Ø§Ù„Ø© Ù‡Ø°Ù‡ Ø§Ù„Ø±ÙˆØ§Ø¨Ø· ÙˆÙ…Ø¯Ù‰ ØªØ£Ø«ÙŠØ± Ø§Ù„Ø³ÙŠØ§Ù‚ ÙÙŠ Ù…Ø¢Ù„Ø§ØªÙ‡Ø§ØŒ ÙˆØ¥Ø¹Ø·Ø§Ø¦Ù‡Ø§ Ù…Ø¹Ø§Ù†Ù Ù…ØªØ¹Ø¯Ø¯Ø© Ø£Ùˆ Ù‚ØµØ±Ù‡Ø§ Ø¹Ù„Ù‰ Ù…Ø¹Ù†Ù‰ ÙˆØ§ØØ¯ØŒ ÙˆÙ…Ù† Ø§Ù„Ø¢Ù„ÙŠØ§Øª Ø§Ù„ØªÙŠ Ø°ÙƒØ±Ù‡Ø§ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ø§Ù„Ø¥ØØ§Ù„Ø© Ù…Ø¹Ø¯Ø¯Ø§ Ø£Ù†ÙˆØ§Ø¹Ù‡Ø§ ÙˆÙ…Ø¨ÙŠÙ†Ø§ Ø£Ù‡Ù…ÙŠØªÙ‡Ø§ ÙˆÙ…Ù† Ø§Ù„Ø¢Ù„ÙŠØ§Øª Ø§Ù„ØªÙƒØ±Ø§Ø± ÙˆØ§Ù„Ø¹Ø·Ù ÙˆØ³ÙŠØªØ¶Ø ÙƒÙ„ Ø°Ù„Ùƒ Ø£Ø«Ù†Ø§Ø¡ Ø§Ù„Ø¨ØØ«. ÙˆÙ‚Ø¯ Ø§ØªØ¨Ø¹ Ø§Ù„Ø¨ØØ« Ù…Ù†Ù‡Ø¬Ø§ ÙˆØµÙÙŠØ§ØŒ ÙˆÙ„ÙƒÙ†Ù‡ Ù„Ù… ÙŠØ¨Ù‚ Ø£Ø³ÙŠØ±Ù‹Ø§ Ù„Ù‡ØŒ Ø¨Ù„ ØØ§ÙˆÙ„ Ø§Ù„Ø¥ÙØ§Ø¯Ø© Ù…Ù† Ø§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ø¢Ø®Ø±Ù‰ Ù‚Ø¯Ø± Ø§Ù„Ø¥Ù…ÙƒØ§Ù†. Ù„Ù‚Ø¯ ØªÙˆØµÙ„ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ù…Ù†Ù‡Ø§Ø› Ø£ÙˆÙ„Ø§: Ø¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… Ù…Ù† Ø£Ù† Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ù„Ù… ÙŠØ°ÙƒØ± Ù„ÙØ¸ Ø§Ù„Ø³ÙŠØ§Ù‚ Ø¥Ù„Ø§ Ø¨Ø¶Ø¹ Ù…Ø±Ø§ØªØŒ Ø¥Ù„Ø§ Ø£Ù†Ù‡ Ø§Ø³ØªØ®Ø¯Ù…Ù‡ ÙƒØ«ÙŠØ±Ù‹Ø§ Ø£Ø«Ù†Ø§Ø¡ ØªÙØ³ÙŠØ±Ù‡ØŒ ÙÙ‚Ø¯ ØªÙ†Ø§ÙˆÙ„ Ù…Ø¹Ø¸Ù… Ø§Ù„Ø¸ÙˆØ§Ù‡Ø± Ø§Ù„Ø³ÙŠØ§Ù‚ÙŠØ© ØªÙ†Ø§ÙˆÙ„Ù‹Ø§ ÙŠÙƒØ´Ù Ø¹Ù† Ø¥Ø¯Ø±Ø§Ùƒ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ù„Ø£Ù‡Ù…ÙŠØ© Ø§Ù„Ø³ÙŠØ§Ù‚ ÙÙŠ ÙÙ‡Ù… Ø§Ù„Ù…Ø¹Ù†Ù‰. Ø«Ø§Ù†ÙŠØ§: Ø£Ø¯Ø±Ùƒ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ø£Ù‡Ù…ÙŠØ© ØªÙ…Ø§Ø³Ùƒ Ø§Ù„Ù†ØµØŒ ÙˆÙ…Ø§ ÙŠØØ¯Ø«Ù‡ Ø§Ù„ØªÙƒØ±Ø§Ø± ÙˆØ§Ù„Ø¥ØØ§Ù„Ø© Ù…Ù† Ø±Ø¨Ø· Ø§Ù„Ù†Øµ Ø¨Ø¹Ø¶Ù‡ Ø¨Ø¨Ø¹Ø¶. ÙˆÙ‚Ø¯ Ø§Ø¹ØªÙ†Ù‰ Ø¨Ø§Ù„Ù…ØØ§Ù„ ÙˆØ§Ù„Ù…ØØ§Ù„ Ø¥Ù„ÙŠÙ‡ ÙˆØ¨ØªØ¹Ø¯Ø¯ Ø§Ù„Ù…ØØ§Ù„ Ø¥Ù„ÙŠÙ‡ØŒ ÙˆØ§Ù„Ø°ÙŠ ÙŠØ¤Ø¯ÙŠ Ø¥Ù„Ù‰ ØªØ±Ø§Ø¨Ø· Ø§Ù„Ù†ØµØŒ ÙÙ‡Ø°Ø§ Ù„Ø§ ÙŠØ¹Ù†ÙŠ Ø£Ù†Ù‡ Ù‚Ø¯ ØªØ±ÙƒÙ‡ Ø¯ÙˆÙ† Ø¶Ø§Ø¨Ø· Ø£Ùˆ Ù‚ÙŠØ¯ Ø¥Ø° ÙŠØ´Ø¯Ø¯ Ø¹Ù„Ù‰ Ø£Ù‡Ù…ÙŠØ© Ù…Ø±Ø§Ø¹Ø§Ø© Ø§Ù„Ø³ÙŠØ§Ù‚ Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØŒ ÙˆÙ…Ø±Ø§Ø¹Ø§Ø© Ø§Ù„Ù†Ø¸Ù… Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØŒ ÙˆÙ„ÙƒÙ† Ø§Ù„Ø¨Ø§ØØ« Ù„Ø§ØØ¸ Ø£Ù† Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ ØÙŠÙ†Ù…Ø§ ØªÙ†Ø§ÙˆÙ„ Ø¸Ø§Ù‡Ø±Ø© Ø§Ù„ØªÙƒØ±Ø§Ø± ØªÙ†Ø§ÙˆÙ„Ù‡ Ù…Ù† Ø¬Ø§Ù†Ø¨ Ø§Ù„Ù…Ø¹Ù†Ù‰ØŒ ÙˆÙˆØ¸ÙŠÙØªÙ‡ Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆÙØ§Ø¦Ø¯ØªÙ‡ Ø¨Ø§Ù„Ù†Ø³Ø¨Ø© Ù„Ù„Ù…Ø®Ø§Ø·Ø¨ØŒ Ø¥Ø° ÙŠØ±Ù‰ Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ø£Ù† Ø§Ù„ØªÙƒØ±Ø§Ø± ÙŠØ¹Ø¯ Ù„ØºÙˆÙ‹Ø§ Ø¥Ù„Ø§ Ø¥Ø°Ø§ Ø£ÙØ§Ø¯ ÙØ§Ø¦Ø¯Ø© Ù„Ù„Ù‚Ø§Ø±Ø¦ØŒ Ø£Ùˆ Ø£Ø±Ø§Ø¯ Ø§Ù„Ù…ØªÙƒÙ„Ù… Ø¥ÙŠØµØ§Ù„ Ø±Ø³Ø§Ù„Ø© Ù„Ù„Ù‚Ø§Ø±Ø¦ Ù…Ù† Ø®Ù„Ø§Ù„Ù‡. Ø«Ø§Ù„Ø«Ø§: Ø§Ù‡ØªÙ… Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ø§Ù‡ØªÙ…Ø§Ù…Ù‹Ø§ ÙƒØ¨ÙŠØ±Ù‹Ø§ Ø¨Ø§Ù„Ø¹Ø·ÙØŒ ÙˆØ¨ÙŠÙ† Ø§Ù„Ø²Ù…Ø®Ø´Ø±ÙŠ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø¹Ø·Ù Ø¹Ù„Ù‰ Ø±Ø¨Ø· Ø£Ø¬Ø²Ø§Ø¡ Ø§Ù„Ù†ØµØŒ ÙˆÙ„Ù… ÙŠÙƒØªÙ Ø¨Ø°Ù„Ùƒ Ø¨Ù„ Ø¥Ù†Ù‡ ÙƒØ§Ù† ÙŠØØ¯Ø¯ Ø¯Ù„Ø§Ù„Ø© ØØ±ÙˆÙ Ø§Ù„Ø¹Ø·Ù ÙˆØ£Ø³Ø¨Ø§Ø¨ Ø§Ø®ØªÙŠØ§Ø±Ù‡Ø§.